RETRACTED: Liposomes: Structure, Biomedical Applications, and Stability Parameters With Emphasis on Cholesterol - Nakhaei, Pooria; Margiana, Ria; Bokov, Dmitry O.; Abdelbasset, Walid Kamal; Jadidi Kouhbanani, Mohammad Amin; Varma, Rajender S.; Marofi, Faroogh; Jarahian, Mostafa; Beheshtkhoo, Nasrin (Frontiers in Bioengineering and Biotechnology, 2021)
Liposomes are essentially a subtype of nanoparticles comprising a hydrophobic tail and a hydrophilic head constituting a phospholipid membrane. The spherical or multilayered spherical structures of liposomes are highly rich in lipid contents with numerous criteria for their classification, including structural features, structural parameters and size, synthesis methods, preparation, and drug loading. Despite various liposomal applications, such as drug, vaccine/gene delivery, biosensors fabrication, diagnosis, and food products applications, their use encounters many limitations due to physico-chemical instability as their stability is vigorously affected by the constituting ingredients wherein cholesterol performs a vital role in the stability of the liposomal membrane. It has well established that cholesterol exerts its impact by controlling fluidity, permeability, membrane strength, elasticity and stiffness, transition temperature (Tm), drug retention, phospholipid packing, and plasma stability. Although the undetermined optimum amount of cholesterol for preparing a stable and controlled release vehicle has been the downside, but researchers are still focused on cholesterol as a promising material for the stability of liposomes necessitating explanation for the stability promotion of liposomes. Herein, the prior art pertaining to the liposomal appliances, especially for drug delivery in cancer therapy, and their stability emphasizing the roles of cholesterol.